The Role of Financial Behavior in Mediateing the Influence of Financial Literacy on Financial Well-Being in The Millennial Generation in Badung Regency - Ayu Intan Dwijayanti, Gusti; Putu Kawiana, I Gede; Sudiana, I Wayan (Lafadz Jaya Publisher, 2023)
The decline in the level of economic growth that occurred in Badung Regency resulted in low financial well-being. This is not only caused by the Covid-19 Pandemic, but also due to the low financial literacy that individuals have in managing their daily finances. The millennial generation is one of the generations that has felt the impact of the economic crisis in their productive age. The purpose of this study was to analyze the role of financial behavior in mediating the effect of financial literacy on financial well-being in the millennial generation in Badung Regency. The research population is the millennial generation in Badung Regency. The sampling technique was carried out by accidental sampling. Questionnaires that have been tested for validity and reliability were given to 100 respondents. The data analysis method used is descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square (SEM-PLS) analysis. The results of this study indicate that variable financial literacy has a positive and significant influence on financial well-being. Financial literacy has a positive and significant influence on financial behavior. Financial behavior has a positive and significant influence on financial well-being. And financial behavior plays a partial role in mediating the effect of financial literacy on the financial well-being of the millennial generation. The research implication is that the millennial generation needs to have financial literacy supported by healthy financial behavior to achieve financial well-being.